(untitled) (Journal of Foreign Language Studies, 2022)
The COVID-19 pandemic is a hot issue that has received much attention worldwide because of its negative impacts on all aspects of society. In this context, the study, in the light of cognitive linguistics, investigates the impacts of the pandemic on the use of media language by investigating cognitive and cultural characteristics of metaphorical expressions about the COVID-19 pandemic containing the source domain of WAR. It, thence, proposes some recommendations for teaching and translation.